STRATEGI STRATEGI KAMPANYE JHON F.KERRY DALAM PEMILU 2 NOVEMBER 2004 - Muhammad Sa'duddin Ashari (Universitas Muhammadiyah Yogyakarta, 2005)
STRATEGI KAMPANYE JHON F.KERRY DALAM PEMILU 2 NOVEMBER 2004